Check-list of the Family Lamiaceae in Pernambuco, Brazil - Almeida,Cecília de Fátima C. B. R. de (2002)
A survey of the family Lamiaceae in the state of Pernambuco revealed the presence of 20 genera encompassing 46 species. The genera with the highest number of exsiccatae were Hyptis and Ocimum; others had little representative material, and some taxa were collected only once. Regarding the phytogeographical distribution in the state, 9.1% of the registrations of species occurred in the coastal zone, 54.5% in the forest zone and 36.3% in the caatinga zone.